2020
DOI: 10.1016/j.stemcr.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Activation Regulates Human Osteoblastogenesis

Abstract: Summary Two genetic diseases, Gorlin syndrome and McCune-Albright syndrome (MAS), show completely opposite symptoms in terms of bone mineral density and hedgehog (Hh) activity. In this study, we utilized human induced pluripotent stem cell (iPSC)-based models of the two diseases to understand the roles of Hh signaling in osteogenesis. Gorlin syndrome-derived iPSCs showed increased osteoblastogenesis and mineralization with Hh signaling activation and upregulation of a set of transcription factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…GO analysis of target genes of this network showed that "mRNA translation and transport" was the most significant biological function in hBMSCs (Figure 6B). In addition, "p53 signaling pathway" and "Hedgehog signaling pathway" were significantly enriched, which have also been suggested to play important roles in osteogenesis (Tyner et al, 2002;Onodera et al, 2020) (Figure 6C). These results further suggested that both lncRNAs and circRNAs could act as miRNA sponge to regulate the expression of downstream genes, which in turn take part in osteogenic differentiation of BMSCs.…”
Section: Construction and Analyses Of Cerna Networkmentioning
confidence: 88%
“…GO analysis of target genes of this network showed that "mRNA translation and transport" was the most significant biological function in hBMSCs (Figure 6B). In addition, "p53 signaling pathway" and "Hedgehog signaling pathway" were significantly enriched, which have also been suggested to play important roles in osteogenesis (Tyner et al, 2002;Onodera et al, 2020) (Figure 6C). These results further suggested that both lncRNAs and circRNAs could act as miRNA sponge to regulate the expression of downstream genes, which in turn take part in osteogenic differentiation of BMSCs.…”
Section: Construction and Analyses Of Cerna Networkmentioning
confidence: 88%
“…The conversion of full-length Gli3 (usually considered as pro-osteogenic) to repressed Gli3 was shown to be reduced not only in Ptch1 +/− mice but also in GS patient-derived induced pluripotent stem (iPS) cells. This inhibitory Gli3 competes with Runx2, a master transcription factor for osteoblast differentiation, for DNA binding, suppresses Runx2 function, and reduces bone formation [ 46 , 48 ].…”
Section: Bone Metabolism Hedgehog Over-activation and Pathologicamentioning
confidence: 99%
“…Patient-derived hiPSCs are also used for in vitro disease modeling and drug screening. Recently, iPSCs derived from patients with GS have been reported by several groups [ 31 , 48 , 117 , 118 , 119 , 120 ]. By using iPSCs derived from patients with GS, a model of abnormal tissue development and tumor formation can be constructed.…”
Section: Disease-specific Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Hedgehog signaling pathway is a conservative and important signaling pathway that participates in various biological metabolism processes in the body [ 23 ]. Studies have shown that the Hedgehog signaling pathway is involved in metabolic processes such as bone formation, metabolism and fracture healing [ 23 , 24 ]. Inhibition of the Hedgehog pathway can lead to fracture nonunion or delayed healing [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%